The development of corporate tax structures in the European Union from 1998 to 2015 - Qualitative and quantitative analysis - Rainer Bräutigam; Christoph Spengel; Kathrin Stutzenberger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Ongoing tax reform processes, competitive pressures and the consequences of the financial and sovereign debt crisis have considerably shaped the tax systems of the Member States of the European Union in the last two decades. Our paper combines a qualitative and quantitative analysis of the development of European tax structures based on a unique and comprehensive dataset for the EU-25 Member States between 1998 and 2015. Especially among the EU-15 Member States, we still find evidence for the often-cited trend of tax rate cut cum tax base broadening. In this context, we identify interest deduction limitation rules and loss provisions as main drivers of tax base broadening. Furthermore, the quantitative analysis of effective tax burden scenarios shows that Member States seem to additionally rely on an increased taxation of dividends to balance possible revenue losses associated with reduced corporate income tax rates.
urn:nbn:de:bsz:180-madoc-435634
Keywords: H20; H25; K34; 330; Tax Policy; Corporate Taxation; European Union